Ciprofloxacin-Resistant Pseudomonas aeruginosa Lung Abscess Complicating COVID-19 Treated with the Novel Oral Fluoroquinolone Delafloxacin. (16th February 2022) - Panholzer, Jürgen; Neuboeck, Matthias; Shao, Guangyu; Heldt, Sven; Winkler, Markus; Greiner, Paul; Fritsch, Norbert; Lamprecht, Bernd; Salzer, Helmut
Abstract : Purpose . We report the development of a lung abscess caused by a ciprofloxacin-resistant Pseudomonas aeruginosa in a patient with COVID-19 on long-term corticosteroid therapy. Successful antimicrobial treatment included the novel oral fluoroquinolone delafloxacin suggesting an oral administration option for ciprofloxacin-resistant Pseudomonas aeruginosa lung abscess. Case Presentation. An 86-year-old male was admitted to the hospital with fever, dry cough, and fatigue. PCR testing from a nasopharyngeal swab confirmed SARS-CoV-2 infection. An initial CT scan of the chest showed COVID-19 typical peripheral ground-glass opacities of both lungs. The patient required supplemental oxygen, and anti-inflammatory treatment with corticosteroids was initiated. After four weeks of corticosteroid therapy, the follow-up CT scan of the chest suddenly showed a new cavernous formation in the right lower lung lobe. The patient's condition deteriorated requiring high-flow oxygen support. Consequently, the patient was transferred to the intensive care unit. Empiric therapy with intravenous piperacillin/tazobactam was started. Mycobacterial and fungal infections were excluded, while all sputum samples revealed cultural growth of P. aeruginosa. Antimicrobial susceptibility testing showed resistance to meropenem, imipenem, ciprofloxacin, gentamicin, and tobramycin. After two weeks of treatment with intravenous piperacillin/tazobactam, the clinical condition improved significantly, and supplemental oxygen could be stopped. Subsequently antimicrobial treatment was switched to oral delafloxacin facilitating an outpatient management. Conclusion . Our case demonstrates that long-term corticosteroid administration in severe COVID-19 can result in severe bacterial coinfections including P. aeruginosa lung abscess. To our knowledge, this is the first reported case of a P. aeruginosa lung abscess whose successful therapy included oral delafloxacin. This is important because real-life data for the novel drug delafloxacin are scarce, and fluoroquinolones are the only reliable oral treatment option for P. aeruginosa infection. Even more importantly, our case suggests an oral therapy option for P. aeruginosa lung abscess in case of resistance to ciprofloxacin, the most widely used fluoroquinolone in P. aeruginosa infection.